Characterizing the evolution of oculomotor and vestibulo-ocular function over time in children and adolescents after a mild traumatic brain injury - Crampton, Adrienne; Schneider, Kathryn J.; Grilli, Lisa; Chevignard, Mathilde; Katz-Leurer, Michal; Beauchamp, Miriam H.; Debert, Chantel; Gagnon, Isabelle J. (Frontiers in Neurology, 2022)
Background Impairments to oculomotor (OM) and vestibulo-ocular reflex (VOR) function following pediatric mTBI have been demonstrated but are poorly understood. Such impairments can be associated with more negative prognosis, affecting physical and mental wellbeing, emphasizing the need to more fully understand how these evolve. Objectives to determine i) the extent to which performance on clinical and computerized tests of OM and VOR function varies over time in children and adolescents at 21 days, 3-, and 6-months post-mTBI; ii) the proportion of children and adolescents with mTBI presenting with abnormal scores on these tests at each timepoint. Design Prospective longitudinal design. Setting Tertiary care pediatric hospital. Participants 36 participants with mTBI aged 6 to18. Procedures Participants were assessed on a battery of OM and VOR tests within 21 days, at 3- and 6-months post injury. Outcome measures Clinical measures: Vestibular/ocular motor screening tool (VOMS) (symptom provocation and performance); Computerized measures: reflexive saccade test (response latency), video head impulse test (VOR gain), and dynamic visual acuity test (LogMAR change). Analysis Generalized estimating equations (parameter estimates and odd ratios) estimated the effect of time. Proportions above and below normal cut-off values were determined. Results Our sample consisted of 52.8% females [mean age 13.98 (2.4) years, assessed on average 19.07 (8–33) days post-injury]. Older children performed better on visual motion sensitivity (OR 1.43, p = 0.03) and female participants worse on near point of convergence (OR 0.19, p = 0.03). Change over time (toward recovery) was demonstrated by VOMS overall symptom provocation (OR 9.90, p = 0.012), vertical smooth pursuit (OR 4.04, p = 0.03), voluntary saccade performance (OR 6.06, p = 0.005) and right VOR gain (0.068, p = 0.013). Version performance and VOR symptom provocation showed high abnormal proportions at initial assessment. Discussion Results indicate impairments to the VOR pathway may be present and driving symptom provocation. Vertical smooth pursuit and saccade findings underline the need to include these tasks in test batteries to comprehensively assess the integrity of OM and vestibular systems post-mTBI. Implications Findings demonstrate 1) added value in including symptom and performance-based measures in when OM and VOR assessments; 2) the relative stability of constructs measured beyond 3 months post mTBI.